Gold Investment by Installment in the Bank Indonesian Sharia Kabanjahe Branch: Analysis of Law No. 21 of 2008 and DSN MUI Fatwa Number 77 of 2010 - Wahyudi Ganda Syahputra; Sri Sudiarti; Hafsah Hafsah (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
Bank Syariah Indonesia Gold Installment products, are in great demand by Bank Syariah Indonesia customers, including those in Kabanjahe, Karo-North Sumatra. This study examines the practice of investing in gold installments that have been regulated in Law No. 21 of 2008 and legitimized by the DSN fatwa of the Indonesian Ulema Council No. 77/DSN/MUI/VI/2020, whose legality is still being debated in Islamic law. The type of research used is field qualitative with a statutory approach and a case approach. The study results show that applying gold installment investments at BSI Kabanjahe complies with the provisions stipulated in Law No. 21 of 2008 concerning Islamic banking. Buying and selling gold in cash, either through ordinary buying and selling or buying and selling murabaha in the perspective of the DSN MUI fatwa Number 77 of 2010, is legally permissible (mubah or ja'iz). Then the solution to the obstacles in implementing gold installment investments at Bank Syariah Indonesia Kabanjahe Branch is to increase promotion and understanding to the public about gold investment products and discipline customers who are disobedient in paying by giving warning letters.